Physical activity to reduce PCSK9 levels - Tirandi, Amedeo; Montecucco, Fabrizio; Liberale, Luca (Frontiers in Cardiovascular Medicine, 2022)
The amount of physical activity (PA) people practice everyday has been reducing in the last decades. Sedentary subjects tend to have an impaired lipid plasma profile with a higher risk of atherosclerosis and related cardio- and cerebrovascular events. Regular PA helps in both primary and secondary cardiovascular prevention because of its beneficial effect on the whole metabolism. Several studies reported lower levels of plasma lipids in trained subjects, but the precise mechanisms by which PA modulates lipoproteins remain only partially described. Thereupon, proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serin protease whose main function is to reduce the amount of low-density lipoprotein cholesterol (LDL-C) receptors, with the direct consequence of reducing LDL-C uptake by the liver and increasing its circulating pool. Accordingly, recently developed PCSK9 inhibitors improved cardiovascular prevention and are increasingly used to reach LDL-C goals in patients at high CV risk. Whether PA can modulate the levels of PCSK9 remains partially explored. Recent studies suggest PA as a negative modulator of such a deleterious CV mediator. Yet the level of evidence is limited. The aim of this review is to summarize the recent reports concerning the regulatory role of PA on PCSK9 plasma levels, highlighting the beneficial role of regular exercise on the prevention of atherosclerosis and overall CV health.